Clinician–Investigator Training and the Need to Pilot New Approaches to Recruiting and Retaining This Workforce - Hall, Alison K. (Acad Med, 2017)
Clinician–investigators, also called physician–scientists, offer critical knowledge and perspectives that benefit research on basic science mechanisms, improved diagnostic and therapeutic approaches, population and outcomes medicine, health policy, and health services, yet few clinically trained health professionals pursue a research career. Sustaining this workforce requires attention to the unique challenges faced by investigators who must achieve clinical and research competence during training and their careers. These challenges include the duration of required clinical training, limited or discontinuous research opportunities, high levels of educational debt, balancing the dual obligations and rewards of clinical care and research, competition for research funding, and the need for leadership development after training. Women and individuals from underrepresented racial and ethnic groups comprise a small percentage of this workforce. The authors summarize the recent literature on training for clinician–investigators, emphasizing approaches with encouraging outcomes that warrant broader implementation. Using this overview as background, they convened three workshops at the National Institutes of Health in 2016 to identify and refine key priorities for potential new pilot programs to recruit and retain the clinician–investigator workforce. From these workshops emerged three priorities for future pilot programs: (1) support for research in residency, (2) new research on-ramps for health professionals at multiple career stages, and (3) national networks to diversify and sustain clinician–investigator faculty. Implementation of any pilot program will require coordinated commitment from academic health centers, medical licensing/certification boards, professional societies, and clinician–investigators themselves, in addition to support from the National Institutes of Health.